Mycophenolate mofetil attenuates uterine ischaemia/reperfusion injury in a rat model - (:unkn) unknown (ELSEVIER SCI LTD, 2017)
This study evaluated the effect of mycophenolate mofetil (MMF) on uterine tissue preservation following ischaemia/reperfusion (I/R) injury. Uterine I/R injury was induced in rats by clamping the lower abdominal aorta and ovarian arteries for 30 min. Group I/R + V (n = 7) received vehicle alone while Group I/R + M (n = 7) received 20 mg/kg/day MMF. Control groups underwent sham surgery and received vehicle (Group C) or 20 mg/kg/day MMF (Group M) (n = 7 for both). Four hours after detorsion, uterine tissue 8-hydroxy-2'-deoxyguanosine (8-OHdG), glutathione, malondialdehyde (MDA), myeloperoxidase (MPO), superoxide dismutase (SOD) and serum ischaemia modified albumin (IMA) concentrations were measured. Histopathological analyses were performed. The I/R + M group showed significant reduction in serum IMA and uterine tissue 8-OHdG, MDA and MPO and significant increase in SOD concentrations compared with the I/R + V group, indicating a protective effect against I/R oxidative damage (P = 0.009, P = 0.006, P = 0.002, P = 0.003 and P = 0.009, respectively). Histopathological evaluation revealed MMF treatment resulted in significantly less tissue and cellular damage and apoptosis compared with the I/R + V group. These results indicate MMF is effective in attenuating uterine tissue damage and preventing apoptosis following uterine I/R injury, probably via anti-inflammatory and anti-oxidative action. (C) 2016 Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: mycophenolate mofetil; oxygen species-free radicals; rat; uterine ischaemia-reperfusion; uterine transplantation; ISCHEMIA-REPERFUSION INJURY; UTERUS TRANSPLANTATION; ISCHEMIA/REPERFUSION INJURY; LIVER-TRANSPLANTATION; OXIDATIVE STRESS; KIDNEY; ADHESION; DONOR; ALLOTRANSPLANTATION; TACROLIMUS